Resveratrol ameliorates oxidative DNA damage and protects against acrylamide-induced oxidative stress in rats - BECEREN, AYFER; ŞENER, GÖKSEL (SPRINGER, 2012)
Acrylamide (ACR), used in many fields from industrial manufacturing to laboratory personnel work is also formed during the heating process through interactions of amino acids. Therefore ACR poses a significant risk to human health. This study aimed to elucidate whether resveratrol (RVT) treatment could modulate ACR-induced oxidative DNA damage and oxidative changes in rat brain, lung, liver, kidney and testes tissues. Rats were divided into four groups as control (C); RVT (30 mg/kg i.p. dissolved in 0.9% NaCl), ACR (40 mg/kg i.p.) and RVT + ACR groups. After 10 days rats were decapitated and tissues were excised. 8-hydroxydeoxyguanosine (8-OHdG) is a biomarker of oxidative DNA damage. 8-OHdG content in the extracted DNA solution was determined by enzyme-linked immunosorbent assay method. Malondialdehyde (MDA), glutathione (GSH) levels and myeloperoxidase activity (MPO) were determined in tissues, while oxidant-induced tissue fibrosis was determined by collagen contents. Serum enzyme activities, cytokine levels, leukocyte apoptosis were assayed in plasma. As an indicator of oxidative DNA damage, 8-OHdG levels significantly increased in ACR group and this was reversed significantly by RVT treatment. In ACR group, GSH levels decreased significantly while the MDA levels, MPO activity and collagen content increased in the tissues suggesting oxidative organ damage. In RVT-treated ACR group, oxidant responses reversed significantly. Serum enzyme activities, cytokine levels and leukocyte late apoptosis which increased following ACR administration, decreased with RVT treatment. Therefore supplementing with RVT can be useful in individuals at risk of ACR toxicity.
Keywords: Acrylamide; Resveratrol; Oxidative DNA damage; 8-Hydroxydeoxyguanosine; Myeloperoxidase; Leukocyte apoptosis; NF-KAPPA-B; APOPTOSIS; CELLS; MYELOPEROXIDASE; EXPRESSION; EXPOSURE